Current Nosology of Neural Autoantibody-Associated Dementia - Hansen, Niels (Frontiers in Aging Neuroscience, 2021)
Background The detection of neural autoantibodies in patients with cognitive decline is an increasingly frequent phenomenon in memory clinics, and demanding as it does a specific diagnostic approach and therapeutic management, it deserves greater attention. It is this review’s aim to present the latest nosology of neural autoantibody-associated dementia. Methods A specific literature research via PubMed was conducted to describe the nosology of neural autoantibody-associated dementia. Results An autoimmune dementia comprises with an early onset, atypical clinical presentation and rapid progression in conjunction with neural antibodies, signs of inflammation in the cerebrospinal fluid, and a non-neurodegenerative pattern in neuroimaging. An autoimmune dementia is probably present if the patient responds to immunotherapy. Atypical dementia involving neural autoantibodies with mostly N-methyl-D-aspartate receptor antibodies might not fulfill all the autoimmune-dementia criteria, thus it may constitute an independent disease entity. Finally, a neurodegenerative dementia such as the frontotemporal type also coincides with neural autoantibodies such as the subunit ionotropic glutamate receptors 3 of amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor antibodies, dementia with Lewy bodies with myelin oligodendrocytic protein, myelin basic protein antibodies, or Creutzfeldt-Jakob disease with Zic4 or voltage gated potassium channel antibodies. These dementia entities may well overlap in their clinical features and biomarkers, i.e., their neural autoantibodies or neuroimaging patterns. Conclusion There are three main forms of neural autoantibody-associated dementia we can distinguish that might also share certain features in their clinical and laboratory presentation. More research is urgently necessary to improve the diagnosis and therapy of these patients, as the progression of their dementia might thus be improved or even reversed.